Estrangeiros nunca mais! Migrantes como sujeitos de direitos na Política de Assistência Social - Damaceno, Silvana Mittmann (2022)
This Dissertation has as its theme international migrations, borders and social assistance. As a general objective, it seeks to analyze the socioeconomic characterization of international migrants who are users of the Social Assistance policy in the municipality of Medianeira - PR, from the approval of the Migration Law (Law No). The study adopted a methodology of quantitative and qualitative research, linked to a bibliographic review, document analysis and access to data from the Single Registry for Social Programs platforms and the Interactive Bank of the Migration Observatory. In its development, it brings theoretical-analytical elements dedicated to understanding the multidimensional social spaces that make up the western Paraná border strip and its relationship with international migrations and commuting by border residents; analyzes the legal-normative frameworks on the migration issue in Brazil and the significant changes, as of 2017, with the approval of the Migration Law; addresses Brazil's participation in multilateral debates on the issue of migration and human rights dealt with in the South American Conferences on Migration (CSM); in the Union of South American Nations (UNASUR) and in the Common Market of the Southern Cone (MERCOSUR), and presents the migratory influx in the municipality of Medianeira-PR and the socioeconomic profile of international migrants, users of the Social Assistance policy municipality in order to answer the following research question: in the context of the increase in migratory flows and the new Migration Law in Brazil, who is the international migrant, user of the Social Assistance policy in the municipality of Medianeira - PR?